Energy Management of Context-aware Cold Chain Vehicle Nodes - Ronling Hu; Xiang Li; Yang Lou; Wei Yan (Universitas Ahmad Dahlan, 2016)
In view of the question that the energy-constrained sensor nodes affect the normal operation of the whole system due to the short survival period, in this paper we present a new solution of adaptive energy management from the angle of context-aware computing. In different scenario modes, we take different environment acquisition and communication strategy according to scenario parameters, and thus build the context-aware energy management model. Finally, we extend the whole system life by lowering energy consumption of single internet of things vehicle node. Experimental data show that the energy management plan of context-aware wireless sensor nodes effectively reduces the energy consumption of nodes and extends the system life under the premise of providing reliable services.